Caught in a Matrix of Factors: A Pilot Study of Female Retirees Receiving Below-Minimum Pension Payments - Bieńkowski, Stefan; Życzyńska-Ciołek, Danuta (Qualitative Sociology Review, 2023)
Pension systems based on an insurance model were originally designed for male breadwinners who worked under permanent contracts without career breaks. Since their inception, women’s participation in the workforce has increased significantly, but on average, their employment career paths are still shorter and less linear compared to those that men enjoy. Demographic changes have prompted many countries to reform their pension systems to ensure long-term financial sustainability. And to varying degrees, such reforms also have looked to address the issue of short careers. In Poland, reforms introduced in 1999 brought about significant changes to the rules governing pension entitlement. That led to the emergence of a new category of retirees—those who had contributed to the pension system for a short period and consequently received very low pensions. This article provides an overview of an exploratory qualitative pilot study conducted in 2018 with nine women who were in receipt of benefits from the Polish universal pension system, which amounted to less than the so-called ‘lowest retirement pension’ being granted at that time. The analysis makes recourse to the concept of employment career and its connection to retirement to identify various life-course determinants that contributed to their situation. These factors include childhood and adolescent adversities that affected educational attainment; domestic and caregiving responsibilities coupled with cultural expectations and insufficient institutional support; the labor market situation, and the inability to document certain employment periods. The research material indicates that a significant portion of the work performed by the interviewees throughout their lives did not translate into a pension benefit, as it either involved unpaid domestic and caregiving duties; or work performed without formal contracts.